Asia's cauldron : The South China Sea and The End of a Stable Pacific - Kaplan, Robert D (New York Random House, 2014)
"An examination of the future role of the South China sea in international relations and a tour of the nations surrounding the South China Sea and their interests in the region. In exploring each of these countries individually, Kaplan clearly shows where the conflicts may arise and why they will be challenging for the international community"
Including Index
Keywords: South China Sea -- International law -- Strategic aspects of individual places -- Pacific Area -- Diplomatic relations